Leitura em língua estrangeira (inglês) para elaboração de resumos documentários - Souza, Vânia Regina Alves de [UNESP] (2002)
Reading in English with the purpose of writing abstracts can be facilitated through ESP (English for specific purposes) approach. The student learns reading strategies that help him in text comprehension without the necessity of having great knowledge in English. This research proposal is to investigate the reading process of a written English text after the students had been acquainted with the two disciplines (ESP and 'Indexing and Abstract') in the Library Science course. We propose an 'interface' between both subjects in order to comprehend English written texts to the task of writing abstracts. The objectives are to contribute to these subjects related to the reading orientation to the abstract writing task and to point out some reading indicators to methodologies suggesting ESP approach. This research was carried out by the analysis of abstract and reading bibliographies and observation of the reading process. The technique of the data collecting was the one denominated Thinking Aloud. The reading process observed was carried out by two students from the fourth grade of Library Science at UNESP in Marília. Both of them had taken the two subjects above mentioned during the course. They received instructions about the use of ESP to overcome problems of the weak language knowledge and also about the synthesis, analysis and representation of the document. We verified how they read a text in order to write an abstract and observed that they used the reading strategies learned in the ESP classes as well as the knowledge about abstract writing. The obtained results indicate that the instrumental approach may be useful to the abstract writing task by means of appropriate reading strategies, such as, vocabulary strategies, language structure, paragraph structure, textual markers, selectivity, metacognitive monitoring, prediction, nominal... (Complete abstract, click electronic address below)